Development of a Research and Service Information System to Optimize Monitoring of Research and Service Activities at Semarang State University - Muh. Sholeh; Anggyi Trisnawan Putra; Martanto Setyo Husodo (Journal of Economic Education, 2023)
The aim of this research is to build a module that contains monitoring features for the stages of research implementation and community service at SIPP to realize effectiveness and efficiency in the process of monitoring the stages of activity implementation by utilizing information system-based technology to support orderly administration and service improvement at LPPM UNNES. This type of research is research and development. Research and development is a process or steps to develop a new product or improve an existing product that can be accounted for. The results of the research show that with the development of the Research and Community Service Information System (SIPP), deficiencies in the previous piecemeal system which was carried out manually or electronically but not in the application of databases can be overcome properly, thereby making the data management process easier. effective and efficient. The SIPP being developed already has data storage media in the form of a database so it is hoped that it can minimize the possibility of data loss. With the development of SIPP, it is hoped that the process of incoming mutations, outgoing mutations, majors, can run well so that data errors do not occur and make it easier for researchers and staff to organize data